PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL BERBASIS FLIM PENDEK TERHADAP KREATIVITAS PESERTA DIDIK KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SDN 22 KOTA BIMA - Meviota Maharani Windi Yuwono; Nunung Fatimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the use of short film-based audio-visual learning media on the creativity of fifth-grade students in Indonesian language subjects at SDN 22, Bima City. This research approach is quantitative research with a pre-experimental type of research with a One Group Pretest-Posttest Design. The population in this study were all fifth-grade students of SDN 22, Bima City, with a sample of 22 fifth-grade students in accordance with the total sampling technique used. Data collection was carried out by tests. Data analysis techniques were carried out using descriptive statistical analysis and inferential statistics. The results obtained from the descriptive analysis are: (1) the use of audio-visual learning media has an effect on student learning outcomes, evidenced by the increased scores of observation results at each meeting; (2) student learning outcomes in the initial test (pretest) are in the moderate category, while student learning outcomes at the end of the learning (posttest) are in the high category. Thus, it can be concluded that the use of audio-visual learning media has an effect on the creativity of fifth-grade students in Indonesian language learning at SDN 22, Bima City.